2019
DOI: 10.1002/jum.15085
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Guided Hydraulic Release Associated With Corticosteroids in Radial Tunnel Syndrome: Description of Technique and Preliminary Clinical Results

Abstract: The aim of this study was to describe a perineural ultrasound-guided infiltration technique for management of radial tunnel syndrome and to report its preliminary results in 54 patients. A mixture of a saline solution, a local anesthetic, and a corticosteroid solution was infiltrated in the perineural region at the arcade of Frohse. Pain was reported in 100% of patients before the procedure versus 1.9% after the procedure. Scratch collapse and Cozen test results were positive in 98.1% and 66.7% of patients bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…García et al provided the largest analysis of ultrasound-guided HD for radial tunnel syndrome with 54 patients (32). The intervention in this retrospective case series was an injection composed of 1 mL of a 5-mg betamethasone dipropionate acetate and 2 mg betamethasone sodium phosphate combination, 2 mL of 2% lidocaine, and 1 to 2 mL of saline solution for roughly 5 mL total volume.…”
Section: Resultsmentioning
confidence: 99%
“…García et al provided the largest analysis of ultrasound-guided HD for radial tunnel syndrome with 54 patients (32). The intervention in this retrospective case series was an injection composed of 1 mL of a 5-mg betamethasone dipropionate acetate and 2 mg betamethasone sodium phosphate combination, 2 mL of 2% lidocaine, and 1 to 2 mL of saline solution for roughly 5 mL total volume.…”
Section: Resultsmentioning
confidence: 99%
“…Perineural hydrodissection is a minimally invasive technique to dissect the perineural plane and tissue space. Currently, there are no high-level studies to determine the effectiveness of hydrodissection; however, low-level studies have demonstrated some effectiveness (3)(4)(5) . In the present study, the patient's symptom began five or more years previously, and 15 weeks after the first hydrodissection, the symptom was fully recovered, with ultrasonography depicting an improvement of the multiple stenotic lesions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Perineural hydrodissection, a new treatment for peripheral neuropathy, is a minimally invasive technique using an injection of fluid to dissect the perineural plane and tissue space. Even though its definite effect has not been sufficiently proven, it has been reported as a potentially useful treatment for various peripheral nerve entrapment syndromes ( 3 5 ) .…”
Section: Introductionmentioning
confidence: 99%
“…A smaller study by Engin et al 32 also showed positive results using steroid injections, with seven of 18 patients requiring surgical intervention because of refractory symptoms after injection. Garcia et al 33 used ultrasonography imaging to better locate the PIN at the AF before injection and found notable improvement in pain after steroid injection, although long-term follow-up was not conducted. Temporary PIN palsy is a possible risk of steroid injections around the nerve, especially because most authors mix local anesthetic and corticosteroid and should be discussed with patients before proceeding.…”
Section: Nonsurgical Treatmentmentioning
confidence: 99%